2023
DOI: 10.3201/eid2905.221541
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence Compared with Confirmed COVID-19 Cases among Children, Colorado, USA, May–July 2021

Abstract: To compare SARS-CoV-2 antibody seroprevalence among children with seropositive confirmed COVID-19 case counts (case ascertainment by molecular amplification) in Colorado, USA, we conducted a cross-sectional serosurvey during May–July 2021. For a convenience sample of 829 Colorado children, SARS-CoV-2 seroprevalence was 36.7%, compared with prevalence of 6.5% according to individually matched COVID-19 test results reported to public health. Compared with non-Hispanic White children, seroprevalence was higher am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We estimated 1.7–2.8 times the number of infections in children from seroprevalence than the reported cumulative incidence in Oregon ( Figure ). This total is a lower degree of underascertainment than had been reported in seroprevalence studies of children during May–July 2021 in the United States ( 1 ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We estimated 1.7–2.8 times the number of infections in children from seroprevalence than the reported cumulative incidence in Oregon ( Figure ). This total is a lower degree of underascertainment than had been reported in seroprevalence studies of children during May–July 2021 in the United States ( 1 ).…”
Section: Discussionmentioning
confidence: 55%
“…However, understanding the true burden of pediatric COVID-19 infection poses a challenge. Children are more likely to have asymptomatic or mild disease, and pediatric infections are, therefore, less likely to be reported to public health authorities ( 1 , 2 ). Clarifying pediatric SARS-CoV-2 prevalence is important because it is well established that children can transmit SARS-CoV-2 to other children and adults ( 3 , 4 ).…”
mentioning
confidence: 99%
“…The scale of affected individuals may be considerable, with the World Health Organization reporting over 750 million confirmed infections worldwide and nearly 7 million deaths [4]. Seroprevalence data further suggest that the actual numbers could be considerably higher, particularly among the pediatric population [5][6][7]. Through the utilization of routine laboratory blood samples for SARS-CoV-2 prevalence monitoring, we previously demonstrated that the true number of infections may be 3.93-5.66 times higher [8].…”
Section: Introductionmentioning
confidence: 99%